Routledge handbook of air power (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2018)
The Routledge Handbook of Air Power offers a comprehensive overview of the political purposes and military importance of air power. Despite its increasing significance in international relations, statecraft and war, the phenomenon of air power remains controversial and little understood beyond its tactical-technological prominence. This volume provides a comprehensive survey designed to contribute to a deep and sophisticated understanding of air power